Efektivitas Project Based Learning Berbantuan Virtual Manipulative Media terhadap Kemampuan Spasial dan Hasil Belajar Matematika - Pradipta Setia Widi Astuti; Aqidatul Munfariqoh; Ahmad Teguh Purnawanto; Fulusia Nurmawati (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) model assisted by Virtual Manipulative Media (VMM) on visual spatial skills and mathematics learning outcomes in two-dimensional geometry. This quantitative research applied a Pre-Experimental Design with a One-Group Pretest-Posttest Design. The research subjects involved all 20 fourth-grade students of SDN 2 Nglobo, selected using a total sampling technique. The research instruments consisted of visual spatial skills and cognitive learning outcomes tests. Data analysis techniques included the Shapiro-Wilk normality test, the Paired Samples T-Test, and the N-Gain Score calculation processed through IBM SPSS. The results indicated that the data were normally distributed, and the paired t-test yielded a t-value of -15.079 with a two-tailed significance value of 0.000 (p < 0.05), which convincingly rejected the null hypothesis and accepted the alternative hypothesis. Furthermore, the group's normalized gain calculation achieved an N-Gain Score of 0.4714 (47.14%), falls into the moderate category. Based on these findings, it can be concluded that the implementation of the PjBL model assisted by VMM is significantly effective in improving visual spatial skills and mathematics learning outcomes of elementary school students on two-dimensional geometry.